Carbonic anhydrase 8 regulates basophil activation and interleukin 4 production - Peng, Jianya; Sy, Chandler B.; Zhao, Siyuan; Sawhney, Arman; Espinosa, Vanessa; Schroeter, Marissa N.; Ponessa, John J.; Chavan, Krupa; Lemenze, Alexander D.; Rivera, Amariliz; Rohacs, Tibor; Siracusa, Mark C. (Frontiers in Immunology, 2025)
Carbonic anhydrase (Car) enzymes are a family of metalloenzymes that are traditionally known for their ability to regulate pH and CO2 homeostasis. However, emerging studies now demonstrate that Car family members exhibit lineage-specific expression patterns within immune cells. Moreover, it has been shown that genetically and pharmacologically targeting specific Car family members is sufficient to regulate immune cell development and activation. This work has identified Car enzymes as viable therapeutic targets that can influence immunity and inflammation. Here we contribute to this growing body of literature and demonstrate that Car8 is highly expressed by basophils and basophil precursor cells compared to other Car family members. While deletion of Car8 had no effect on basophil development or recruitment, mice deficient in Car8 were protected from basophil- and interleukin (IL)-4-dependent atopic dermatitis-like inflammation. Consistent with these findings, Car8-deficient basophils exhibit defects in the cytokine-stimulated release of IL-4 that is associated with altered calcium signaling pathways. Collectively, these studies reveal the lineage-specific expression patterns of Car8 and its unappreciated function in regulating basophil activation.